New instrumental platform for the exploitation of the field-dependence of T 1 in rock core analysis and petroleum fluids: application to T 1-T 2 correlation maps - Korb, Jean-Pierre; Ferrante, Gianni; Bubici, Salvatore; Mallett, Mike (Diffusion Fundamentals, 2014)
We propose using the latest wide bore fast field cycling NMR relaxometers for measuring the nuclear magnetic relaxation dispersion (NMRD) profiles of the logarithmic average proton-water <1/T1> in carbonate rock cores samples of 1 inch diameter and in different crude oil/brine mixings. The observed bilogarithmic frequency behaviours of the NMRD have been interpreted with a proposed theoretical model yielding a measurement of the water local wettability at the pore surface. We have also proposed a NMR platform that uses a variable wide-bore cryogen-free superconducting magnet to acquire 2D T1-T2 correlation spectrum of a mixing of bulk water and crude oil pools. Such a T1-T2 plot allows quantitative separation of mixed bulk water and crude oil. The 2D plot does not reveal any exchange between the different and independent pools.